Responses of Mast Cells to Pathogens: Beneficial and Detrimental Roles - Jiménez, Mariela; Cervantes-García, Daniel; Córdova-Dávalos, Laura E.; Pérez-Rodríguez, Marian Jesabel; Gonzalez-Espinosa, Claudia; Salinas, Eva (Frontiers in Immunology, 2021)
Mast cells (MCs) are strategically located in tissues close to the external environment, being one of the first immune cells to interact with invading pathogens. They are long living effector cells equipped with different receptors that allow microbial recognition. Once activated, MCs release numerous biologically active mediators in the site of pathogen contact, which induce vascular endothelium modification, inflammation development and extracellular matrix remodeling. Efficient and direct antimicrobial mechanisms of MCs involve phagocytosis with oxidative and non-oxidative microbial destruction, extracellular trap formation, and the release of antimicrobial substances. MCs also contribute to host defense through the attraction and activation of phagocytic and inflammatory cells, shaping the innate and adaptive immune responses. However, as part of their response to pathogens and under an impaired, sustained or systemic activation, MCs may contribute to tissue damage. This review will focus on the current knowledge about direct and indirect contribution of MCs to pathogen clearance. Antimicrobial mechanisms of MCs are addressed with special attention to signaling pathways involved and molecular weapon implicated. The role of MCs in a dysregulated host response that can increase morbidity and mortality is also reviewed and discussed, highlighting the complexity of MCs biology in the context of host-pathogen interactions.